"A Not-so-silent Form of Activism": Intentional Community as Collective Action Reservoir. Issue 4 (November 2021) - Rubin, Zach
Recent scholarship on social movement groups has increasingly focused on the relationships between lifestyle and politics. As walls of classical social movement theories holding up the false dichotomy of personal and political spheres continue to crumble, I seek in this article to fill some of the space connecting personal and political work by expanding on the concept of collective action reservoirs. Based on an ethnographic case study of an intentional community named Dancing Rabbit Ecovillage, I demonstrate how participation in a shared lifestyle can be the basis for a politicized account of everyday life. The members of this village have developed a unique lifestyle that they consider to be a form of political engagement, in which I show that they have different orientations to the definition of activism and to being in a "reserve guard" for direct action. They have developed and adopted an approach where lifestyle is the primary means of seeking change while direct action is held in reserve. I conclude by theorizing that the collective action reservoir represents a long-term stable base for social movement mobilizations.